Magnetic parameters of Fe–Al–Ga ternary system: Ab initio calculations - A.F. Abdullin; E.V. Voronina; L.V. Dobysheva (Учёные записки Казанского университета: Серия Физико-математические науки)
Quantum mechanical calculations of the magnetic parameters in the ternary system Fe–Al–Ga for different contents of Al and Ga were carried out. The equilibrium values of the lattice constant, as well as the average values of magnetic moments and hyperfine magnetic fields were calculated. It was shown that the change in the magnetic parameters during the replacement of aluminum with gallium is mainly due to a change in the lattice parameter. The results obtained were compared with the experimental data.